2010
DOI: 10.1007/s00198-010-1355-6
|View full text |Cite
|
Sign up to set email alerts
|

Deleting Rac1 improves vertebral bone quality and resistance to fracture in a murine ovariectomy model

Abstract: Our results demonstrate that the deletion of Rac1 increases vertebral bone quality compared to WT bones in a postmenopausal osteoporosis model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…13 Although the results are somehow conflicting and their precise function not elucidated yet, both Rac1 and Rac2 seem to be important for the formation of the podosome belt and for bone resorption. 31,[63][64][65][66] This confirms earlier studies showing podosome belt disruption in osteoclasts where Rac1 and Rac2 have been neutralized by specific antibodies. 67 Using DNA microarray, we analyzed the expression profile of 76 GEFs of the Dbl and Dock families in osteoclasts.…”
Section: Adhesion Structuressupporting
confidence: 88%
See 1 more Smart Citation
“…13 Although the results are somehow conflicting and their precise function not elucidated yet, both Rac1 and Rac2 seem to be important for the formation of the podosome belt and for bone resorption. 31,[63][64][65][66] This confirms earlier studies showing podosome belt disruption in osteoclasts where Rac1 and Rac2 have been neutralized by specific antibodies. 67 Using DNA microarray, we analyzed the expression profile of 76 GEFs of the Dbl and Dock families in osteoclasts.…”
Section: Adhesion Structuressupporting
confidence: 88%
“…Although the authors agree on the increase in bone density, there are discrepancies regarding the mechanisms involved that will need further investigation. 31,[63][64][65] Interestingly, the absence of a single Rac GEF, such as Vav3, Dock5 or FARP2, is sufficient to result in osteoclasts impaired resorption in vivo, through distinct mechanisms. [68][69][70] The higher bone density observed in mice deficient for Rho GTPase signaling highlights them as targets in diseases with increased bone resorption such as post-menopausal osteoporosis or cancer-associated osteolysis.…”
Section: Resultsmentioning
confidence: 99%
“…During osteoclast resorption cycle, 伪v尾3 integrins signalling induces Dock5 recruitment to the Src/Pyk2/p130Cas complex which ultimately leads to Rac1 activation and localisation to the sealing zone [Vives et al., ]. Dock5 plays an important role in this pathway because its deletion in knockout mice results in increased trabecular bone mass due to an impaired osteoclasts ability to assemble podosomes into sealing zones [Vives et al., ], a phenotype also observed in knockout mice for Rac1 [Croke et al., ; Magalhaes et al., ] and some of its guanine exchange factors [Faccio et al., ; Takegahara et al., ]. Interestingly, a group working on allergy showed that Dock5 is essential for the dynamic rearrangement of microtubules during mast cell degranulation in anaphylactic responses [Ogawa et al., ].…”
Section: Introductionmentioning
confidence: 99%
“…During osteoclast resorption cycle, 伪v尾3 integrins signaling induces Dock5 recruitment to the Src/Pyk2/p130Cas complex which (Nagai et al, 2013). Dock5 plays an important role in this pathway because its deletion in knockout mice results in increased trabecular bone mass due to an impaired osteoclasts ability to assemble podosomes into sealing zones (Vives et al, 2011), a phenotype also observed in knockout mice for Rac1 (Croke et al, 2011) (Magalhaes et al, 2011 and its guanine exchange factors (Faccio et al, 2005) (Takegahara et al, 2010. Interestingly, a group working on allergy showed that Dock5 is essential for the dynamic rearrangement of microtubules during mast cell degranulation in anaphylactic responses (Ogawa et al, 2014).…”
mentioning
confidence: 99%